Survival of Pseudomonas aeruginosa in various carriers for the inhibition of root rot-root knot disease complex of mungbean - Imran Ali Siddiqui (Phytopathologia Mediterranea, 2001)
The survival of Pseudomonas aeruginosa strain 78 was tested on mungbean seeds coated with a variety of substrates/carriers and was found best on talc amended with carboxymethyl cellulose or on gum arabic. Albizia saman- and Cordia myxa-gum gave poor survival. On all substrates the antagonist populations declined dramatically at 120 days after coating. In the repeating experiments, a seed coating with talc-based inoculum of the antagonist caused marked reduction in nematode population densities in the soil and roots and also reduced subsequent root-knot development due to Meloidogyne javanica, the root-knot nematode. However, the incidence of the rootinfecting fungi Macrophomina phaseolina and Rhizoctonia solani did not differ significantly from the controls. Strain 78 significantly promoted growth with increased Bradyrhizobium-nodules in mungbean.